Critical care in the emergency department: monitoring the critically ill patient. Issue 7 (22nd June 2006) - Andrews, F J; Nolan, J P
Abstract : The aim of monitoring patients is to detect organ dysfunction and guide the restoration and maintenance of tissue oxygen delivery. Monitoring is a crucial part of the care of the critically ill patient in the emergency department as the physiological response to critical illness is linked strongly to outcome. As it is important to appreciate the limitations of monitoring systems and monitored data, and to understand that invasive monitoring may be hazardous, this review concentrates on the techniques used to monitor critically ill patients in the emergency department. End tidal carbon dioxide monitoring, pulse oximetry, arterial blood pressure monitoring, central venous pressure monitoring, continuous central venous oxygenation saturation monitoring, temperature monitoring, and urine output are discussed. Practitioners should be familiar with the physiology and technology underlying these monitoring techniques and be aware of the pitfalls in interpretation of monitored data.